FEATURES OF PROFESSIONAL SELF-REGULATION DETERMINED BY THE CONSTITUTIONAL COURT OF THE REPUBLIC OF LITHUANIA AND THEIR ASSESSMENT - Vitkutė, Evelina Agota (Teisė, 2017)
The article analyses constitutional basis of professional self-regulation and features of professional self-regulation bodies as they are specified in the jurisprudence of the Constitutional Court of the Republic of Lithuania. It is concluded that the constitutional basis of professional self-regulation should be further developed by referring it not only to freedom of association but also to state institutional system. In addition, it is evaluated that defined features of professional self-regulation bodies sufficiently reveal peculiarities of such bodies and allow forming the concept of such bodies that would clearly allow separating them from ordinary associations.